Pharmacists’ Experiences on Adverse Drug Reactions in Saudi Arabia: A Cross-Sectional Study - Dalal Salem Bakheit Aldossari; Naeema Taha Alshalaan; Khuloud Salem Alshammari; Fatima Ahmed Lubbad; Mudhi Ratyan Alanazi; Neamah Ahmed Lubbad; Nada Suliman Fahad Alessa; Sheraz Ali (Pharmacy)
Background and objectives: As part of Vision 2030, Saudi Arabia aims to strengthen its healthcare system by enhancing efficiency, reducing medical errors, and ensuring drug safety. Evidence on pharmacists’ experiences with adverse drug reactions (ADRs) in daily practice remains limited. Gaining insight into their perspectives is essential for improving patient safety and optimizing pharmaceutical care. Therefore, we aimed to assess pharmacists’ ability to identify ADRs in daily practice and the subsequent actions taken upon identification. Methods: Between July and August 2024, an email-based invitation was sent to randomly selected registered community and hospital pharmacists in Saudi Arabia to participate in the study, which employed a piloted questionnaire. Results: The study involved 305 pharmacists, including 169 hospital/clinical pharmacists (HCPs, 55.4%) and 136 community pharmacists (CPs, 44.6%). A majority (n = 251, 82.3%) indicated direct patient encounters, while 67.2% (n = 205) reported observing suspected ADRs in the preceding 12 months. Most respondents filed ADR reports to the Saudi Food and Drug Administration/National Pharmacovigilance Centre (HCP = 103, CP = 60) and hospital drug information centers (HCP = 89, CP = 64), with online forms being the favored mode (HCP = 122, CP = 96). Awareness of ADR reporting procedures was reported by 128 HCPs and 80 CPs. Conclusions: More than two-thirds of participants reported having participated in ADR reporting, with greater adherence observed in hospital settings. Pharmacists predominantly depend on the Saudi Food and Drug Administration/National Pharmacovigilance Centre and hospital drug information centers for reporting, with a preference for online submission methods. Targeted educational interventions addressing gaps in knowledge, reporting procedures, and form complexity could improve ADR reporting practices. These findings support the need for structured training and policy measures to strengthen pharmacovigilance system.